Elementary School Teacher's Competence in Technology Integration and Curriculum Comprehension - Widiansyah, Apriyanti; Farhana, Husna; Maharbid, Dian Anggraeni (International Conference on Elementary Education, 2025)
The integration of information and communication technology (ICT) into education has become a crucial component of 21st-century teaching competencies. Elementary school teachers are now expected to develop adaptive skills in utilizing digital tools while demonstrating a comprehensive understanding of the current educational curriculum, particularly the Merdeka Curriculum implemented in Indonesia. This study aims to examine teachers’ competencies in adapting to technological advancements and their level of curriculum comprehension within the context of elementary education. Employing a descriptive qualitative design, data were collected through classroom observations, in-depth interviews, and document analysis. The findings reveal that most teachers have demonstrated adequate proficiency in employing digital learning tools, such as online learning platforms, interactive media, and technology-based presentation software. However, variations remain in teachers’ capacity to plan, implement, and evaluate technology-integrated instruction. Moreover, teachers’ understanding of the Merdeka Curriculum has improved through professional development programs, peer collaboration, and participation in learning communities. These results highlight the necessity of continuous professional training focused on both digital literacy and pedagogical competence to ensure effective, innovative, and contextually relevant learning experiences. Strengthening teachers’ technological and curricular expertise is therefore essential to achieving sustainable educational transformation aligned with national and global educational goals.